Juha in Arabic and Turkish Literature A Comparative Literary Study - İbrahim Alşibli; Mahmud Kaddum (Darulfunun Ilahiyat)
Varied repositories of international literature attend to Juha’s anecdotes as an aspect of collective memory and as national symbols appropriated by their cultures. The reality-mocking humorous situations and philosophical distinctiveness of the anecdotes permeated the fabric of popular culture. The stories were also incorporated into varied rhetorical forms such as novels, children’s fiction, cartoons, proverbs, and folk tales. This study accords due recognition to the importance and stability of this figure in the popular culture of Arabs and Turks, adopting Juha as a subject for study, analysis, and comparison in Arabic and Turkish literature. It comparatively investigates the literary figure of Juha in Arabic literature as a central character of the Arab and Turkish cultures. From the comparative perspective, this literary study encompasses Juha’s presence as an effective and influential character in the Arab and Turkish works of literature. It probes the circulation of anecdotes related to Juha in the literary, cultural, and social contexts of Arabs and Turks, and examines the growing employment of Juha tales in multiple literary genres. Despite the historical precedence of the Arab Juha, Nasr al-Din Khoja al-Turki’s features distinguished him from the Arab Juha in aspects including the themes of anecdotes, the places of their occurrence, the personalities who contributed to the event, and the formulation and presentation of the overall vision. The paper is arranged in three sections. Initially, it introduces the characters of Juha Al-Arabi and Nasr Al-Din Khoja Al-Turki and references Arab and Turkish sources to outline their histories. Second, it delves into the structure of anecdotes: the characters, their natures, the roles they discharge in the narrative exposition, and how they interact with events as protagonists producing linguistic signs and ideas. The paradox is familiar. This section of the paper also focuses on the locational structure of the anecdotes, the aesthetics of the place, and how it functions to advance events. The element of time is also analyzed, demonstrating the temporal aspects of the development of events and the representation of the historical stages at which the anecdotes occurred. The third section presents the similarities and differences between the Arab and Turkish anecdotes and the ways in which the accounts are represented in Arabic and Turkish literature. Finally, the paper concludes by iterating the study’s most significant results.